Growing platforms within platforms: How platforms manage the adoption of complementor products in the presence of network effects? - Agarwal, Shiva; Miller, Cameron D.; Ganco, Martin (Strategic Management Journal, 2023)
Abstract Research Summary Platform owners often use endorsements to actively manage complementor firms. We argue that the direct network effects of complementors' products play a central role in the platform management by its owner. We test our predictions using data on the Apple's promotion of apps. We find that apps with network effects are more likely to receive an award. This likelihood increases when the app is introduced by a developer with a larger market share but declines when introduced in a concentrated segment. The likelihood decreases further if the app is introduced in a concentrated segment by a developer that holds a larger market share. Further, we observe that in concentrated segments, the “challenger” developer has a higher likelihood of receiving the award relative to the leader. Managerial Summary Many products offered through platforms have their own direct network effects. The value of the product for each user grows with the number of other consumers using the product. Many platform owners also actively manage their platforms to ensure platform growth and often use less traditional tools such as product endorsements to achieve this goal. In the context of video games listed in the iOS App Store and the Editors' Choice Awards as a form of product endorsement, we examine the tradeoffs that products with direct network effects (i.e., multiplayer video games) present to the platform owner (Apple). On the one hand, the platform owner may want to promote apps with direct network effects to help them achieve a momentum in terms of user growth. On the other hand, networked apps may become dominant in the segment with negative implications for future growth of the segment and the platform owner's profitability. We find evidence consistent with this tension and find that it critically depends on the complementor strength and market segment concentration. We also observe that in concentrated segments, the “challenger” developer has a higher likelihood of receiving the award relative to the leader.